Covid-19 Influences On The Productivity Of Construction Projects - Lekha, S. Balakrishnan (Universiti Sains Malaysia, 2021)
Covid-19 is a worldwide pandemic that has altered the global economic landscape. The ongoing epidemic is the primary cause of job losses of the construction workers. The impact of Covid-19 on the construction industry from the productivity perspective is examined in this study. In the global pandemic of Covid-19, the construction industry and its economic prospects are also considered. The secondary research examines the influence of coronavirus in conjunction with other factors. The survey sample included more than 5 construction related firms in Malaysia which consist of 60 respondents. There were 29 questions in total, divided into six categories. Firm executives were approached by phone or WhatsApp and asked to complete self-administered questionnaires via an online survey platform. The data was analysed by Microsoft Excel. The major impact of Covid-19 pandemic on the construction industry in terms of productivity perspective is manpower (job loss). As highlighted by the respondents, “many employees lost their job during this pandemic since the implementation of the movement control order (MCO)”. Most of the respondent which is around 53.3% of people answered strongly agreed and 18.3% of people agreed for this statement. Moreover, the manpower aspect was perceived as the most significant impact of Covid-19 pandemic based on the highest score with the RII value of 4.20. It is vital to enact regulations that would significantly reduce the impacts such as job losses for the workers, allowing them to survive this difficult situation and ensuring back to normal economy condition.